PEDAGOGICAL CONDITIONS FOR ACTIVATING STUDENTS' OUTSIDE-COURSE LEARNING ACTIVITIES THROUGH DIGITAL TECHNOLOGIES (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article clarifies the concept of pedagogical conditions and proposes pedagogical conditions for activating students' extracurricular educational activities using digital technologies.